Trust and workplace spirituality on knowledge sharing behaviour: perspective from non-academic staff of higher learning institutions - Rahman, Muhammad Sabbir; Osman-Gani, AAhad M.; Mat Daud, Nuraihan; Chowdhury, Abdul Hannan; Hassan, Hasliza (Emerald, 2015)
This empirical research aims to, to add value in the existing research on knowledge sharing, investigate the antecedents of knowledge-sharing behaviour by embedding trust and workplace spirituality variable on non-academic staff from higher learning institution in Malaysia. The role of trust, perceived risk and workplace spirituality towards knowledge-sharing behaviour has attracted significant attention from researchers and practitioners to facilitate the culture of knowledge sharing in organization settings. Design/methodology/approach – The units of analysis include non-academic staffs who are currently working in different higher learning institutions in Malaysia. Apart from descriptive study, this research applied confirmatory factor analysis and structural equation modelling. Findings – The result revealed that there is a strong relationship between workplace spirituality and knowledge-sharing behaviour. On the other hand, the perceived risk variables partially mediate the association between trust and knowledge-sharing behaviour. Research limitations/implications – This research is a cross-sectional study. As a result, the limited sample size in this study may have an effect on the power of generalizability. Further research may be necessary to confirm the model across different industry to reveal the nature of the knowledge-sharing behaviour among the staff. Practical implications – The findings from this research could help the policymakers and the respective authorities of higher learning institutions to create a knowledge-sharing culture that is needed to support knowledge sharing and knowledge management within the higher learning institutions. Originality/value – This research not only adds value to knowledge-sharing literature but also used the variable like workplace spirituality under the context of Malaysian higher learning institution. Keywords Workplace spirituality, Trust, Perceived risk, Higher learning institutions, Knowledge-sharing behaviour Paper type Research paper